Semantic analysis of literary works in selected song lyrics and poems at English textbooks for grade XI of senior high schools - Untsa Rohmah Fadzillah; Nur Afifah Fajar Satiti; Ani Susanti; Tengku Intan Suzila Tengku Syarif (BAHASTRA, 2022)
This study aims to discover the semantic meaning focused on non-literal meaning of figurative language found in selected literary works of song lyrics and poems in the English Textbooks Grade XI of Senior High School published by Tiga Serangkai and the Ministry of Education and Culture. This study applied a descriptive qualitative method. The results of the study indicated several types of figurative language such as metaphor, hyperbole, simile, personification, depersonification, symbol, antithesis, litotes, alliteration, with the highest frequencies are metaphor and hyperbole, while the lowest frequencies are depersonification and symbol. As for the High Order thinking skill practice, it should be seen by implementing song lyric and poem materials in the teaching and learning process which include observation, question, association, experiment, and network. Therefore, it suggested an analysis evaluation and assessment provided in school textbooks to see the use of the textbooks with High Order Thinking Skill (HOTS) practices.